6 - La crise et la théorie du développement: Quelles fonctions sociales - ACER Bourenane Ν (Africa Development, 1983)
In the years, the term «crisis» seems to have acquired a universal dimension. One can hardly enumerate the social domains in which the term is not frequently used. In this paper, we propose to examine what is today referred to, at the international level, as the «crisis of development». One point on which there seems to be unanimous agreement among social scientists, politicians and economic agents is the fact of the unhealthy state of the world economic system. The malaise affects developed capita list countries, planned economies as well as underdeveloped economies with the problem of unemployment, underemployment, weak performance of the productive sectors and low rates of growth. In the underdeveloped countries, indebtedness, poverty, famines, the generalization of dictatorships and the institution of violence as a method of government, are considered by all as a menace to international stability. Taking these indicators at their face value, it is difficult to resist the temptation of characterizing the situa face value, it is difficult to resist the temptation of characterizing the situa tion as apocalyptic. A closer examination of these indicators, however, reveals two problems: a) the validity of the figures, usually furnished by international organizations, concerning the socio-economic situation especially in the underdeveloped countries, eg. the number of inhabitants who annually die of hunger, and b) the interpretation of the figures, once they are establi shed as being more or less valid. For example, the rates of unemployment in Western Europe and North America currently are often considered abnor mally high. Some analysts even go as far as characterizing the situation as being insupportable. Yet these rates are not anywhere near the highest ever recorded in the history of capitalism. Furthermore, compared to the situa tion in the underdeveloped countries, unemployment figures in the If est appear ridiculously low. To use social indicators indiscriminately to characterize of the international economic system as being in tely question whether the crisis is a myth or a reality are its true dimensions. In any case, it is difficult for use to accept the notion of crisis being applied systematically and mechanically to the world capitalist system where expansionary and recessionary movements are structural. The notion could be applied to the current situation only under the assumption that we are witnessing the final phase of capitalism, which is clearly hard to accept. To overcome a crisis means to return to a situation characterized by harmonious relations between the various elements that constitute a totality; in short, to return to a situation of equilibrium deemed desirable. Inevitably, therefore, the indicators used to demonstrate « a crisis of socie ty», of the economic system, as well as the vision of the desirable equili brium situation, are first and foremost from the point of view of the domi nant social groups and not those of the whole society. The generalized use of the notion of crisis, presumably affecting all the components of a system in a similar manner, therefore, serves to divert attention from the internal contradictions wihtin the system. Its social role is to ensure the reinforce ment and the internationalization of relations of domination. The notion of crisis also serves very well the theoreticians of deve lopment, national and international institutions and universities, specialized in the domain of development studies. In this context, «crisis» becomes a magic word, a potion whose usage permits them to gloss over the failure of development strategies based on absurd models, and to justify the produc tion of «new» schémas and development strategies. The last two decades have witnessed at the highest instance of the international community — the United Nations — the elaboration and pursuit of two international strategies of development. The first strategy — that of the sixties — was based on an implicit postulate that development has an exclusively economic character, and that primacy belongs to economic growth, reduced to increases in production. Development was viewed as a uniform and non-conflictual process and the following principles were accepted unchallenged: Foreign investment and international aid consti tute a necessary condition for increasing the rate of accumulation, growth is an exclusive function of capital formation, industry is the motor of growth, and development planning is better left to specialists and technocrats. The second development decade abandons growth in favour oj elimination of poverty, employment, income distribution and the partici pation of the «masses» in the decision — making process. Development is no longer conceived as growth and capital formation but as the satisfac tion of basic human needs. But the modifications in the strategy of deve lopment which we witness between the sixties and, the seventies were not solely due to the failures of the first development decade. These modifications concide with the parallel evolution of the theory of development, as opposed to the economies of development, as well as the coming into being of a potential alternative model to the liberal model; namely, the model of a planned economy. A critical analysis of the theory and models of development of the past two development decades, can be situated at many levels. Three, at least, merit to be presented because they demonstrate the superficial character underlying the analysis. The first level relates to the terminology utilized. It demonstrates the incapacity of the theory to cope with complex social reality. The reality is reduced to a series of simple factors which constitute «obstacles» or necessary conditions for development. The second level concerns the hypotheses on which the models are based. These are for the most part contestable or debatable. This is espe cially the case with the assumed relationships between savings and profit, savings and investment, the substitutabiUty between factors of production as well as the neutrality of international relations, the world market, of ins titutions and transnational corporations. The third level concerns the mo dels themselves. Aside from their abstraction from reality, they are mecha nistic. Thus, relations between economic aggregates have the same signifi cance in all societies, regardless of the diversities in economic and social structures. More and more, it becomes obvious that it is these theories that are facing a crisis, and it explains the proliferation of new theories (often accompanied by a great deal of confusion); the most notable of which is the approach which seeks to add a new dimension — the cultural dimension — to discussions on development issues. Henceforth, development is not viewed as social and economic but evolves from «human development» to «integral development». Countries are no longer underdeveloped or over developed but simply mat-developed due to insufficiency or excess of the development potion. This new approach is interesting from many angles: First, it attempts to respond to reactions (often violent) against the tendency towards homogenization and cultural domination. Secondly, it puts the problems of the centre and the periphery of the world capitalist system on the same footing. If there is a crisis, it is a crisis of mal-development which affects both the centre and the periphery. Thus international relations, and in particular, the relations between the centre and the periphery cease to be conflictuaL Rather, it is «international solidarity» that is called for in order to overcome the crisis of the international system. Finally, the «human being» and not the «social being» being at the heart of this approach, all direct intervention (by international institutions), in the affairs of populations deemed to be in danger can be justified. It is this approach that has given rise to global strategies in the areas of food, health, education, culture etc. Thus for example, in the area of food, we have a world «food plan». fPe are only left with the question as to who is to handle the production, with what means, and to whose benefit Bourenane ΝACER, Enseignant de Sociologie - Institut des Sciences Sociales, Alger